The Impact of Mobile Applications on Foreign Languages Acquisition: A Pedagogical Perspective - Majzoub, Islam (Technium Social Sciences Journal, 2025)
The onset of mobile applications has changed language learning, providing new chances for acquiring foreign languages. This paper examines the impact of mobile applications on foreign language acquisition from a pedagogical perspective. It explores how the integration of mobile technology in language learning encourages engagement, accessibility, and effectiveness for learners of different age groups and proficiency levels. Mobile apps offer individualized learning experiences through interactive features such as multimedia, gamification, content, and real-time feedback, making language acquisition more engaging and adjustable. moreover, the paper discusses the role of mobile applications in upgrading autonomy and self-directed learning, enabling learners to practice language skills outside traditional classroom environments. Despite the advantages, challenges such as the digital divide, over-reliance on technology, and the need for structured pedagogical frameworks are also addressed. The paper concludes by emphasizing the possibility of mobile applications as a valuable tool in foreign language education, suggesting that their pedagogical application requires careful combination into curricula for optimal learning outcomes.